Temperature Regulation and Immersion - Craig, A. B. (Biomechanics and Medicine in Swimming, 1983)
A recently published bibliography titled Man in the Cold Environment contains about 500 abstracts, most of which have appeared in the literature since 1972 (Schilling, 1980). There were, of course, many other earlier publications which were not included. It is not possible to cover the entire subject of thermoregulation in a cold environment and my review must therefore be limited. The aim of this article is to discuss temperature regulation in water as it relates to competitive and recreational swimmers. Man's normal environment is air, but people enter the water for many reasons, including rehabilitation, recreation, and competitive sports. Many physiological responses are different in air than in water, but for swimmers the most important factor is heat exchange between the water and the body.